Ancillary Tests - Pınar Zeyneloğlu; Süha Bozbay (Galenos Yayinevi, 2023)
Ancillary tests are the tests those help to confirm the clinical diagnosis of brain death. These tests are in 2 groups as electrophysiological and tests for the evaluation of cerebral blood circulation. They indicate the absence of cerebral blood circulation and brain electrical activity. They should not replace clinical evaluation.